Предмет: Математика,
автор: minkimo67mo708
(3a²b-4ab³) : (5ab)
(27k⁴l⁵+21k³l²):(-10k³l²)
Ответы
Автор ответа:
6
Пошаговое объяснение:
1) (3a²b - 4ab³) : (5ab) =ab(3a - 4b²) : 5ab = (3a - 4b²) : 5; 2) (2c⁵b⁴ + 3c⁴b³) : ( -3c⁴b³) = c⁴b³( 2cb + 3) : ( -3c⁴b³) = - 1/3 (2bc + 3) = - 2/3bc - 1; 3) ( - 27(k⁴¹)⁵ + 21(k³¹)²) : ( -10(k³¹)² = ( - 27k²⁰⁵ + 21k⁶²) :- 10k⁶² = 2,7k¹⁴³ - 2,1; 4) ( - a⁵b³ + 3a⁶b²) : 4a⁴b² = - ( a⁵b²(b + 3a)) : 4a⁴b² = - 0,25a(b + 3a)
minkimo67mo708:
ёмаё спасибо
Похожие вопросы
Предмет: Русский язык,
автор: иимп
Предмет: Технология,
автор: Аноним
Предмет: Английский язык,
автор: milana48
Предмет: Алгебра,
автор: KirilkaKirill
Предмет: Физика,
автор: floyd98